(untitled) (Community Based Medical Journal, 2019)
We are reporting a rare case with ankylosing spondylitis (AS), renal impairment with IgA nephropathy. Here, we discuss the course of diagnosis. A 32 year-old man with bilateral pain of the sacroiliac joints for 5 years and leg swelling for 10 days. A Diagnosis of AS by HLA-B27 and pelvic X-ray tests, pathological diagnosis and IgA nephropathy based on renal biopsy. We administered methylprednisolone 500 mg/d for 3 consecutive days, followed by methylprednisolone 40 mg oral QD for a month. The patient was followed up once a month. In the sixth month, the patient’s serum creatinine had decreased to 0.96 mg/dL, urine microalbumin creatinine ratio decreased to 173.3 mg/g, and albumin had risen to 33.1 g/L. Pain and morning stiffness were relieved. Although the causal relationship between AS and IgA nephropathy in this patient still needs to be established. In clinical practice, patients with AS need to be screened for renal complications. CBMJ 2019 January: vol. 08 no. 01 P: 39-43